Early epigenetic downregulation of WNK2 kinase during pancreatic ductal adenocarcinoma development - Dutruel, Céline; Bergmann, Frank; Rooman, I.; Zucknick, Manuela; Weichenhan, Dieter; Geiselhart, Lea; Kaffenberger, Tina; Rachakonda, P. Sivaramakrishna; Bauer, Anton; Giese, Nathalia; Hong, C.; Xie, Huaping; et al. (Oncogene, 2014)
Pancreatic ductal adenocarcinoma (PDAC) is usually incurable. Contrary to genetic mechanisms involved in PDAC pathogenesis, epigenetic alterations are ill defined. Here, we determine the contribution of epigenetically silenced genes to the development of PDAC. We analyzed enriched, highly methylated DNAs from PDACs, chronic pancreatitis (CP) and normal tissues using CpG island microarrays and identified WNK2 as a prominent candidate tumor suppressor gene being downregulated early in PDAC development. WNK2 was further investigated in tissue microarrays, methylation analysis of early pancreatic intraepithelial neoplasia (PanIN), mouse models for PDAC and pancreatitis, re-expression studies after demethylation, and cell growth assays using WNK2 overexpression. Demethylation assays confirmed the link between methylation and expression. WNK2 hypermethylation was higher in tumor than in surrounding inflamed tissues and was observed in PanIN lesions as well as in a PDAC mouse model. WNK2 mRNA and protein expressions were lower in PDAC and CP compared with normal tissues both in patients and mouse models. Overexpression of WNK2 led to reduced cell growth, and WNK2 expression in tissues correlated negatively with pERK1/2 expression, a downstream target of WNK2 responsible for cell proliferation. Downregulation of WNK2 by promoter hypermethylation occurs early in PDAC pathogenesis and may support tumor cell growth via the ERK-MAPK pathway.
published online 5 August 2013
Gesehen am 23.07.2020